Analysis of Disaster Knowledge, Preparedness, and Perceptions on Mitigation Strategies in Kota Sabang Urban Development Planning as a Disaster-Prone Tourist Destination - Nur Akmal, Muhammad; Sunarty, Risma; Farysyi Ishak, Sayed (Sumatra Journal of Disaster, Geography and Geography Education, 2024)
ABSTRACT: This study aims to analyze the knowledge, preparedness, and perceptions of the community regarding appropriate and effective disaster mitigation strategies in the urban development planning of Sabang City, a tourist destination vulnerable to natural disasters such as earthquakes, tsunamis, and floods. The research employs a qualitative approach. Data were collected through in-depth interviews with various stakeholders, including government officials, community leaders, and tourists. The results indicate that the level of knowledge and preparedness for disasters among the population in Sabang City varies significantly, with the majority of respondents displaying low awareness and preparedness levels. Factors such as education level and previous disaster experience were found to have a significant influence on community preparedness. Furthermore, the existing mitigation strategies in Sabang City have not been fully effective, particularly in terms of public awareness, education, disaster-resilient infrastructure development, and inter-agency coordination. Keywords: Disaster Knowledge, Preparedness, Perceptions on Mitigation Strategies, Sabang City